International business, sustainability and corporate social responsibility - Gonzalez-Perez, Maria-Alejandra.; Leonard, Liam. (Bingley, U.K. : Emerald, 2013)
This is the first in a two volume study of Corporate Social Responsibility and corporate behaviour from around the world, taking in viewpoints from five continents and over ten countries. These case studies present a detailed analysis of best practice in the corporate world in the areas of social ethics and community engagement.
Corporate social responsibility and international business : a conceptual overview / Maria Alejandra Gonzalez-Perez -- Global civil society and international business : a review / Maria Alejandra Gonzalez-Perez -- International business, corruption, and bribery / Duane Windsor -- Institutional and market forces : the dominant logic of strategic corporate responsibility and innovative value co-creation / Frederick Ahen, Peter Zettinig -- The influence of corporate social responsibility (CSR) activities on building corporate reputation / Emel Esen -- Creating the global greenscape : developing a global market-entry framework for the green and renewable technologies / Margee Hume ... [et al.] -- Conflicting forces for internationalization of hydropower equipment producers : reconciling sustainability and CSR with MNEs' international strategies / Lilach Nachum, Michael Schmid -- Review of strategic policy framework for re-evaluating 'CSR' programme impacts on the mining-affected areas in India / A.N. Sarkar.
Print version record
Keywords: Business & Economics -- Business Ethics; Business ethics; Sustainability; Social responsibility of business; Sustainability